Analisis Disiplin Kerja, Lingkungan Kerja, dan Motivasi Kerja serta Pengaruhnya terhadap Kinerja Karyawan pada Wyndham Tamansari Jivva Resort Bali - Ni Kadek Sayang Murjayasri; I Wayan Siwantara; I Gusti Ayu Widiadnyani (Jurnal Manajemen Riset Inovasi, 2026)
Human resources are a vital asset for a company, playing a central role in supporting the achievement of organizational goals through optimal performance. Therefore, companies need to pay attention to various factors that can affect employee performance, such as work discipline, work environment, and work motivation. This study aims to analyze the influence of work discipline, work environment, and work motivation, both partially and simultaneously, on employee performance at Wyndham Tamansari Jivva Resort Bali. This research uses probability sampling with a proportionate stratified random sampling technique, involving a sample of 86 respondents drawn from all active employees. The data sources consist of primary and secondary data, and the type of research is quantitative. Data were collected through observation and questionnaires measured using a Likert scale, while the instrument was tested using validity and reliability tests. The data analysis technique used is multiple linear regression. The results indicate that, both simultaneously and partially, work discipline, work environment, and work motivation have a positive and significant effect on employee performance at Wyndham Tamansari Jivva Resort Bali. This shows that the better the work discipline, work environment, and work motivation, the higher the employee performance.